Biochemical Analysis of the Complex between the Tetrameric Export Adapter Protein Rec of HERV-K/HML-2 and the Responsive RNA Element RcRE pck30 - Langner, Janina S. (American Society for Microbiology, 2012)
The RNA export adaptor protein Rec, encoded for by the human endogenous retrovirus HERV-K/HML-2 elements, binds to the Rec responsive element (RcRE) located in the 3′ untranslated region of HERV-K/HML-2 transcripts. Binding allows the nucleocytoplasmic export of unspliced viral RNA, thereby overcoming host restriction. Chemical probing of the secondary structure of the RcRE corroborated the theory that the RcRE forms a complex folded structure with seven stem-loop regions. Laser-induced liquid beam ion desorption mass spectrometry revealed that Rec forms stable tetramers, which are further stabilized upon RNA binding. The RNA protein complex consists of three Rec tetramers, which bind to multiple sites on the RcRE—preferentially to purine-rich motifs—which represent several low-affinity binding sites. Mutated RcREs, with one to three purine-rich motifs deleted, were still bound and exported by Rec, indicating that the complex folded structure of the RcRE is important for Rec binding. This suggests a binding model where up to three Rec tetramers bind to the complex folded structure of the RcRE and the binding seems to be tightened by recognition of the purine-rich motifs.